Consumer Preferences Onthe Sponge Cake Made of Warm Wateras A Substitute For Fat - Gusnadi, Dendi (International Journal of Engineering and Technology, 2019)
This study examined the level of consumersâ€™ preference for the sponge cake made up of warm water. In the process of making sponge cake, besides flour, egg, and sugar, fat usually functions as the major component. The flavor of a cake is generally affected by the quantity of the used fat and eggs. However, fat is commonly shunned because of its negative impacts on the human body. Hence, this paper analizes the level of consumer preferences for sponge cake when fat as its main ingredient is replaced with warm water. This study employed an experimental method by which the collected data were analyzed with ANOVA. In the future, such a production of sponge cake made of warm water is expected to become an innovative and creative formulation of sponge cake desired by the consumers.Â